Evolution Of Piling Design And Techniques In Mudstone At Manchester Airport - Colin Curtis (Deep Foundations Institute, 2001)
In recent years, Manchester Airport has undergone expansion including the construction of a second runway, a new terminal building (Terminal 3) and extensions to the existing Terminal 1. Manchester is Britains third largest airport and ranked 20th in the world for international traffic. Arup (Manchester) was engaged as consulting engineer in a multi-disciplinary role for the terminal works. Part of this was a geotechnical commission including site investigation and pile design followed by supervision. This paper reviews the piling for the old, new and terminal extensions. In total, five pile types have been utilised over the years. The original 1950's Terminal 1 was founded on driven cast in situ piles, with a later 1970's extension utilising rotary augured piles. The recent piling comprised continuous flight auger piles (CFA), driven steel tube and tripod bored; the latter in areas of restricted access or low headroom. The ground conditions are Made Ground over thin Alluvial and Glacial drift, in turn, over a generally weak to moderately weak gypsiferous mudstone. All the piles were socketed into the mudstone. In terms of the new CFA piles, quality control using the instrumentation monitoring was problematical, but a substantial static load and integrity test programme resolved pile performance. Part of the work is matching new pile performance with previously installed piles and the continued use of older piles with new loads. Research provided some data on the older piles, including some static load test data, which enabled back analyses of their design and likely behaviour. Differences in design methods, installation techniques and pile behaviour based on load tests will be discussed.